DEIKSIS BAHASA MELAYU SAMBAS DALAM FILM KEMBANG POLARIA - Rosanti, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstrackThere are many forms of words to express the same meaning is the interesting thing studied by researchers especially in the study deiksis. The problem in this research is how deiksis persona, place deiksis, and deiksis time in Sambas Malay language. The purpose of this study is to describe the deixis persona, place deixis and deiksis time in Malay sambas. Data analysis techniques by the author as follows: film transcription, translation into the Indonesian language, classify data, and analyze data (analyze data by listening video film Kembang Polaria 1 and two, recorded transcription of Malay Sambas dialogue, translate from Sambas Malay to Indonesian, classifies deixis persona, place deixis, and time deixis, discusses the results of analysis with the first supervisor and second supervisor, summarizes the results of data analysis). Based on data analysis, the research concludes as follows: Deiksis persona in Kembang Polaria film can be divided into three based on the role of people involved in the conversation. There are eighteen deiksis persona in the film Flower Polaria four deiksis first persona single, two deiksis first person plural (inclusive and exclusive), three deiksis second person singular, two in plural, six deiksis persona third person. In the plural there is one. There are eighteen deiksis place in the film Kembang Polaria, proximal deiksis nine, semi-proximal nine, and distal 4. There are sixteen deiksis time in film Kembang Polaria can be divided into three based on talker's time that is dextical proximal time two, semi proximal in five, and distal time ten. Keywords: deiksis, persona, place, time, Sambas Malay